2021
DOI: 10.1186/s12935-021-01888-x
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin role as cell-signaling pathways modulator: implications in cancer prevention and treatment

Abstract: Cancer is a complex disease orchestrated by various extrinsic and intrinsic pathways. In recent years, there has been a keen interest towards the development of natural extracts-based cancer therapeutics with minimum adverse effects. In pursuit of effective strategy, a wide variety of natural products-derived compounds have been addressed for their anticancer effects. Apigenin is a naturally-occurring flavonoid present abundantly in various fruits and vegetables. Decades of research have delineated the pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 100 publications
0
42
0
1
Order By: Relevance
“…Curcumin, resveratrol, metformin, melatonin, apigenin and some others are examples that have been shown to sensitise cancer cells to therapy while reducing toxicity to normal tissue/cell. [13][14][15][16][17][18][19][20] In this review, we focus on the effects of curcumin on the induction of cell death in cancers. Some cancers may show resistance to a type of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, resveratrol, metformin, melatonin, apigenin and some others are examples that have been shown to sensitise cancer cells to therapy while reducing toxicity to normal tissue/cell. [13][14][15][16][17][18][19][20] In this review, we focus on the effects of curcumin on the induction of cell death in cancers. Some cancers may show resistance to a type of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Apigenin is one of the most abundant flavonoids in plant kingdom and therefore has been the target of various investigations for its use as anticancer agent and for its role in cancer prevention [ 102 , 103 , 104 ]. In these studies, the compound showed anticancer potential via induction of apoptosis and cell cycle arrest as well as the downregulation of matrix metalloproteinases and interaction with miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, the compound showed anticancer potential via induction of apoptosis and cell cycle arrest as well as the downregulation of matrix metalloproteinases and interaction with miRNAs. However, apigenin was also found to undergo rapid elimination, thus raising the need for, e.g., nanoformulations to increase its bioavailability [ 104 ]. The compound has been studied for its effect on U266 and RPMI8226 cell lines and primary MM cells, where it inhibited proliferation (without affecting healthy PBMCs), influenced cell cycle progression and induced programmed cell death [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/PTEN/AKT/mTOR pathway can become unusually activated in several human cancers. Its activation can enhance cancer cell proliferation, tumour growth, angiogenesis, and survival, making it the most common route through which bioactive components induce apoptosis in cancer cells [ 35 ]. The signaling cascades get stimulated by either B and T cell receptors, receptor tyrosine kinases, cytokines, G-protein-coupled receptors (GPCRs), integrins, and other stimuli such as insulin and other growth factors.…”
Section: Cancer Microenvironmentmentioning
confidence: 99%